Deepening local democracy in Latin America : participation, decentralization, and the left - Goldfrank, Benjamin (University Park : The Pennsylvania State University Press, 2011)
"Addresses the question of why institutions meant to attract citizen participation succeed in strengthening civil society and improving state responsiveness and transparency in some places, but fail in others. Focuses on urban politics in Porto Alegre (Brazil), Montevideo (Uruguay), and Caracas (Venezuela)"--Provided by publisher.
Democracy, participation, and decentralization -- A tale of three cities -- Caracas : scarce resources, fierce opposition, and restrictive design -- Montevideo : from rousing to regulating participation -- Porto Alegre : making participatory democracy work -- Stronger citizens, stronger state? -- Conclusion : the diffusion of participatory democracy and the rise of the left.
Includes bibliographical references (p. [267]-291) and index.
Keywords: Political participation -- Latin America -- Case studies; Municipal government -- Latin America -- Case studies; Comparative government -- Case studies; Porto Alegre (Rio Grande do Sul, Brazil)) -- Politics and government; Montevideo (Uruguay) -- Politics and government; Caracas (Venezuela) -- Politics and government